Moda i hipsterstwo. Hierarchie statusu we współczesnym społeczeństwie konsumpcyjnym - Iwasiński, Łukasz (Człowiek i Społeczeństwo, 2015)
Consumption in sociology is often considered a manifestation of status. According to Pierre Bourdieu, individuals determined by habitus and class dispositions, by consuming certain goods and the style of consumption, consciously or not, demonstrate their status. Bourdieu recognized the uniform hierarchy of status derived from a class structure. Today, this perspective is contested. It is difficult to reconcile it with theories stating class dehierarchization and individualization of society, especially with postmodern concepts. This does not mean that consumer behaviors lost its distinctive function. However, the criteria of distinction (and therefore the source of the status hierarchy) do not necessarily have a class background. In today’s world they are more relativized, more ephemeral and determined by cultural factors. The article examines the source of the status hierarchy in contemporary consumer societies, indicating the role of fashion and the phenomenon of “hip” (“cool”).